Green Banking And Green Economy Sustainability - Wibowo, Fatria Ulfa (Tawazuna, 2023)
Currently, the environmental dilemma is an issue that continues to be discussed in various countries. Climate change, natural disasters, and global warming are claimed to be the result of people's lack of awareness of the environment. The emergence of various environmental problems is a special concern for various parties, including economic activity actors, thus giving rise to the Green Economy plan. The method in this article is library research using several books, journals, and reports as authorship references. The green economy aims to accelerate innovation and investment in sustainable development. Some parts of the green economy are an overall part of sustainable development. Banking globally is also implementing green banking practices, which are increasingly evolving as a banking approach to addressing environmental issues. Banks play a role in providing funding for projects and investments that have the potential to cause environmental damage. Conclusion in this article Green economy is economic development that prioritizes safety and environmental sustainability, provides benefits in the short and long term (sustainable), and reduces inequality for current and future generations and aims to accelerate innovation and investment in sustainable development. Similarly, in the banking sector, banks are responsible for supporting infrastructure development and investment that can damage the environment.